'Transient' genetic suppression facilitates generation of hexose transporter null mutants in Leishmania mexicana. Issue 2 (10th December 2012) - Feng, Xiuhong; Rodriguez‐Contreras, Dayana; Polley, Tamsen; Lye, Lon‐Fye; Scott, David; Burchmore, Richard J.S.; Beverley, Stephen M.; Landfear, Scott M.
Summary The genome of Leishmania mexicana encompasses a cluster of three glucose transporter genes designated LmxGT1, LmxGT2 and LmxGT3. Functional and genetic studies of a cluster null mutant (Δlmxgt1‐3) have dissected the roles of these proteins in Leishmania metabolism and virulence. However, null mutants were recovered at very low frequency, and comparative genome hybridizations revealed that Δlmxgt1‐3 mutants contained a linear extrachromosomal 40 kb amplification of a region on chromosome 29 not amplified in wild type parasites. These data suggested a model where this 29‐40k amplicon encoded a second site suppressor contributing to parasite survival in the absence of GT1‐3 function. To test this, we quantified the frequency of recovery of knockouts in the presence of individual overexpressed open reading frames covering the 29‐40k amplicon. The data mapped the suppressor activity to PIFTC3, encoding a component of the intraflagellar transport pathway. We discuss possible models by which PIFTC3 might act to facilitate loss of GTs specifically. Surprisingly, by plasmid segregation we showed that continued PIFTC3 overexpression was not required for Δlmxgt1‐3 viability. These studies provide the first evidence that genetic suppression can occur by providing critical biological functions transiently. This novel form of genetic suppression may extend to other genes, pathways and organisms.